EVALUATION OF HONORARY TEACHER WELFARE PROGRAMME: A REVIEW OF RECENT LITERATURE - Busanwir Busanwir; Rahmat Shodiqin (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this evaluation is to review the recent literature on welfare programmes for guru honorer. This review provides an overview of the efforts that have been made to improve the financial and non-financial welfare of honorary teachers, as well as the challenges that remain in their implementation. Research results from this literature review show that financial incentives such as salary increases and additional allowances have a positive impact on honorary teachers' motivation and performance, although their distribution is still uneven. In addition, non-financial aspects such as training and professional development were also identified as important factors in improving honorary teachers' teaching competencies and skills. However, access to these training programmes is still limited, especially in remote areas. The conclusion of this review emphasises the need for a more holistic and inclusive strategy to improve the welfare of guru honorer, which includes increased wages, provision of allowances and better access to professional training. Co-operation between the government, educational institutions and local communities is essential to achieve equitable welfare for honorary teachers in Indonesia.